2006
DOI: 10.1167/iovs.05-0458
|View full text |Cite
|
Sign up to set email alerts
|

A Femtosecond Laser Creates a Stronger Flap than a Mechanical Microkeratome

Abstract: The FS laser produces greater corneal stromal inflammation than the MM early postoperatively without any increase in apoptosis and stronger flap adhesion late postoperatively. Therefore, it may require stronger anti-inflammatory drugs to be administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 21 publications
2
63
1
Order By: Relevance
“…Knorz and Vossmerbaeumer 20 compared the adhesive strengths of flaps created with an Amadeus microkeratome and a femtosecond laser (150 kHz) in rabbits. Like Kim et al, 9 they found that flap adhesion was stronger in the femtosecond laser flaps. Netto et al 8 examined early postoperative wounds in LASIK flaps created with a femtosecond laser (15 kHz, 30 kHz, and 60 kHz) and a Hansatome microkeratome in rabbits.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Knorz and Vossmerbaeumer 20 compared the adhesive strengths of flaps created with an Amadeus microkeratome and a femtosecond laser (150 kHz) in rabbits. Like Kim et al, 9 they found that flap adhesion was stronger in the femtosecond laser flaps. Netto et al 8 examined early postoperative wounds in LASIK flaps created with a femtosecond laser (15 kHz, 30 kHz, and 60 kHz) and a Hansatome microkeratome in rabbits.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies 8,9 have confirmed that postoperative inflammation of corneal wound healing and flap configurations differ between these 2 flap-creating methods. 8 These factors might result in distinct anatomic changes, leading to myopic regression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The separation between the laser affected area and the undisrupted collagen fibrils was easily discernible in corneas treated with firingpattern A and B. In corneas treated with firingpattern C (posterior surface centripetal, anterior surface centripetal), the border between the laserdisrupted tissue and the unaffected collagen fibrils became more difficult to discern because of the increased disruption of the fibrils.…”
mentioning
confidence: 91%
“…The aim of the current study was to compare the changes in corneal curvature after different techniques of refractive surgery for myopic correction 25,26 ; that is, LASIK using a microkeratome (Moria M2) and LASIK using a femtosecond laser (IntraLase FS, IntraLase Corp.). These changes could be caused in part by the biomechanical response of the corneal surface after the flap cut and repositioning 27,28 and might have an impact on the refractive outcomes and the refractive stability of LASIK surgery.…”
mentioning
confidence: 99%